THE STRUCTURE OF MIXED SURFACTANTS ADSORBED AT THE AIR LIQUID INTERFACE, AS STUDIED BY SPECULAR NEUTRON REFLECTION - Cummins, P; Penfold, J; Thomas, R; Simister, E; Staples, E (1992)
The specular reflection of neutrons is now finding widespread application in a range of problems in surface chemistry. Recent studies have shown that by the use of hydrogen-deuterium isotopic substitution, it is possible to determine surface excesses and detailed surface structures of surfactants adsorbed at the air-liquid interface. Recent results on the adsorption of mixed nonionic/cationic surfactants at the air-liquid interface are presented. © 1992.